True identity of Folkmanovius paralellus Dobroruka (Chilopoda: Geophilomorpha: Geophilidae) - Tuf, Ivan Hadrián; Dányi, László (Zootaxa, 2015)
The mysterious monotypic genus Folkmanovius Dobroruka, 1957, and its type species, Folkmanovius paralellus Dobroruka, 1957, have never been found again since their description, although the patria of these taxa—the Czech Republic—is among the best studied regions regarding Chilopoda. Analysing the characters given in the original description, we found Folkmanovius to be in the closest relation with another European genus, Clinopodes C.L. Koch, 1847. Some characters could fit with the only Central European representative of this latter genus (Clinopodes flavidus) if, and only if, we consider that the description was based on juvenile specimens. Studying C. flavidus specimens of the first adolescens stadia, we found morphological changes during postembryonic development for several characters, documented first time for the genus. These results explain and elucidate all the tentative differential characters of Dobroruka’s taxa and prove that Folkmanovius Dobroruka, 1957, is a junior subjective synonym of Clinopodes C.L. Koch, 1847, (syn. nov.), as well as Folkmanovius paralellus Dobroruka, 1957, being a junior subjective synonym of Clinopodes flavidus C.L. Koch, 1847 (syn. nov.).